Preparation of start-upers: problems and their solutions - Меlnychenko, V. (Problems of Engineer-Pedagogical Education, 2018)
The importance of the introduction of new technologies and bringing innovative products to the market in the development of the national economy is defined. The list of institutions, resources and conditions of the appropriate preparation of start-upers is concretized. The list of current economic, methodological, organizational, legal, and social problems, existing in this field, is summarized. A list of arrangements for solving these problems is proposed, namely, teaching based on the integration of academic education and innovational activity; engagement of representatives of different specialities for the participation in start-up projects; combination of education with practical activity of entrepreneurs; engagement of skilled pedagogues, who have their own practical experience in developing and launching start-ups, in the preparation of future start-upers; provision of tax reductions to ventures and preferential loans to business angels, who invest resources in this process; provision of real help from the government and business during the stage of launching of the best start-ups.